Chile despertó - The reasons for the mass protests in Chile 2019/2020 - Lea Sasse (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
Starting on 18 October 2019, Chile experienced the largest mass protests in its history. The movement was immensely broad in its demands and diverse in tactics and participants. The citizens' discontent went beyond solely one issue, addressing a more equal welfare system and social justice, among other things. But it was not only about street protests; the social movement also caused an avalanche in social media exchanges and initiated a dialogue among Chileans in the form of neighbourhood associations. This paper argues that long-standing inequalities, the inability of politics to address them, a growing distancing of the population from politics, and the process of the citizens' politicisation were the reasons for the mass protests.
Keywords: O54; I38; Z13; N36; 330; Social movements; Chile; inequality; mass protests; civil society; Latin America; social media; political opportunities; social justice